Mobility Restriction Policy and Poverty Impact of Covid-19 in Indonesia: Evidence from District-Level Data - Wiryawan, Bangkit A. (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
This paper analyze the poverty impact of Covid-19 on regions of Indonesia using district-level data. Six provinces employed non-pharmaceutical measure namely PSBB (Pembatasan Sosial Berskala Besar) mobility restriction are set as the treated group. Meanwhile, our poverty variable is the share of population living below the poverty line against district total, calculated based on the basic needs approach. We employ difference-in-difference (DID) estimator to explore the poverty impact. Results state that while the Covid-19 impact is significant in the more industrialized and globally connected regions such as Java and Bali, provinces implementing PSBB policy suffer from 0.07 – 0.09 percentage points higher poverty incidence compared to the control. The impact is observed to be larger in the urban (city) area compared to the non-urban (districts). The finding suggests inadequacies of the government’s complementary responses in controlling poverty increase, suggesting the need for a more inclusive strategy such as implementing Universal Basic Income.